Landscape structure and breeding bird distribution in a sub-Mediterranean agro-ecosystem - Farina, Almo (Landscape Ecology, 1997)
Richness, abundance and distribution of birds were investigated in the Aulella watershed, a mountainous area of 300 km2 , located in the extreme northwestern corner of Tuscany, Italy in spring and summer, 1995. The study area encompasses five vegetation types (from Mediterranean maqui to upland beech forest) and three main land use categories (woodlands, mixed cultivated + urban areas, montane prairies). The recent history of land abandonment in the study area has produced a rapid expansion of shrubland and woodland, reducing cultivated areas to small patches interspersed in a woodland matrix. Richness, abundance and distribution of birds recorded at 414 points, randomly selected along secondary roads, and located using a Global Positioning System (GPS), were compared with topography, vegetation type and land use in a Geographic Information Systems (GIS) with a grid cell resolution of 200 × 200 m. Bird richness (55 species in all) and abundance are correlated: (a) negatively with the increasing altitude and increasing distance from cultivated areas; (b) positively with the increasing distance from woodlands and mountain prairies. Slope orientation appears to have a negligible effect on bird assemblages. Bird richness and abundance are significantly correlated with vegetation type. Cultivated areas support the highest bird richness and abundance that increase with patch size of the cultivated areas. Local extinction and/or reduction in within-species abundance of birds are expected to continue if the process of land abandonment continues.
Keywords: aulella watershed; geographic information systems; global positioning system; sub-mediterranean agro-ecosystem; tuscany